Chromosome Deletion of 14q32.33 Detected by Array Comparative Genomic Hybridization in a Patient with Features of Dubowitz Syndrome - Darcy, Diana C.; Rosenthal, Scott; Wallerstein, Robert J. (Case Reports in Genetics, 2011)
We report a 4-year-old girl of Mexican origins with a clinical diagnosis of Dubowitz syndrome who carries a de novo terminal deletion at the 14q32.33 locus identified by array comparative genomic hybridization (aCGH). Dubowitz syndrome is a rare condition characterized by a constellation of features including growth retardation, short stature, microcephaly, micrognathia, eczema, telecanthus, blepharophimosis, ptosis, epicanthal folds, broad nasal bridge, round-tipped nose, mild to moderate developmental delay, and high-pitched hoarse voice. This syndrome is thought to be autosomal recessive; however, the etiology has not been determined. This is the first report of this deletion in association with this phenotype; it is possible that this deletion may be causal for a Dubowitz phenocopy.